A method for preparing modified activated carbon with high regeneration rate and high specific surface area
Through oxidant activation and silicon sol superhydrophobic emulsion treatment, a hydrophobic modification method that does not block the activated carbon pores is solved, the pore structure blockage problem is improved, the regeneration rate and moisture-proof performance of activated carbon are achieved, and the high specific surface area and good adsorption performance are achieved.
Patent Information
- Application Number
- CN202211506968.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-29
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-11-29
AI Technical Summary
The existing activated carbon modification methods will lead to blockage and shielding of pore structures, reduce their specific surface area and regeneration rate, and lack moisture-proof performance in high humidity environments.
The surface of activated carbon is activated by oxidizing agents, and the preparation of superhydrophobic emulsion is performed using cetyl trimethylammonium bromide aqueous solution and acid silica sol. The three-dimensional network skeleton structure is formed by hydrolysis and cross-linking to avoid pore blockage and in hydrochloric acid solution. Further treatment was made to remove unreacted inorganic substances and pore reamers.
The hydrophobic activated carbon with high regeneration rate and high specific surface area has been achieved, and the moisture-proof performance has been significantly improved. The adsorption volume increased by 3 to 5 times in high humidity environments, the moisture-absorbing weight gain is less than 10%, the acoustic performance is maintained well, and the pore structure is not damaged.
Smart Images

Figure CN116173910B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing modified activated carbon with high regeneration rate and high specific surface area. Background Art
[0002] For the surface modification of activated carbon, the main focus of previous work has been on improving the targeting of adsorption and increasing the porosity. Research on how to improve the hydrophobicity of activated carbon materials and thus enhance their moisture-proof ability is gradually becoming a hot topic of research. Kim et al. from Sungkyunkwan University deposited polydimethylsiloxane (PDMS) on the surface of activated carbon fibers by vapor deposition, effectively improving the hydrophobicity of activated carbon fibers, and further studied their adsorption performance for toluene under high humidity conditions. The results show that the activated carbon fibers modified by vapor deposition still have good selective adsorption for toluene in a high humidity environment. Liu et al. from the Chinese Academy of Environmental Sciences used the thermal evaporation method and also selected PDMS to hydrophobically modify the activated carbon particles, studying the effect of the treatment process at different temperatures on the pore size of the activated carbon. At the same time, the adsorption performance for benzene was measured under different humidity environments. It was found that the modification had little effect on the pores, and there was obvious selective adsorption of benzene, with certain moisture-proof properties. Liu et al. from Tsinghua University used wet chemical methods to modify mesoporous silica adsorption materials, removing surface hydroxyl groups and functionalizing phenyl groups, which significantly enhanced its hydrophobicity and provided better selective adsorption of toluene under high humidity conditions. Zhu Chaosheng et al. from China University of Petroleum used Dow Corning 184 as a modifier and used vapor deposition to prepare a hydrophobic coating on the surface of activated carbon fibers. While conducting dynamic water adsorption tests, they also studied its adsorption performance for dichloromethane. The problem with existing modification methods is that they cause significant blockage and shielding of the pore structure of activated carbon materials. Summary of the invention
[0003] Purpose of the invention: The purpose of the present invention is to provide a method for preparing a hydrophobic modified activated carbon without blocking or shielding the pore structure of the activated carbon. The super-hydrophobic nano-coating on the modified activated carbon prepared by the method does not block or shield the pore structure of the activated carbon, so that the activated carbon still has a high specific surface area, a high regeneration rate and good moisture-proof performance.
[0004] Technical solution: The method for preparing modified activated carbon with high regeneration rate and high specific surface area of the present invention comprises the following steps:
[0005] (1) Activating the surface of activated carbon using an oxidant;
[0006] (2) soaking the activated carbon in an aqueous solution of hexadecyltrimethylammonium bromide, so that the surface of the activated carbon is charged with cations;
[0007] (3) Acidic silica sol with a particle size of 4 to 10 nm and a solid content of 15 to 20% is added to water, and after ultrasonic treatment, anhydrous ethanol is added (anhydrous ethanol can reduce the surface tension of the solvent system so that perfluorosiloxane can be completely dispersed in the solvent), and tetraethyl orthosilicate is added after mixing, and stirring is continued. Finally, perfluorosiloxane is dropped and stirred in a water bath (heating can promote the hydrolysis of perfluorosiloxane so that it can react and graft with the surface of silica sol nanoparticles) to obtain a superhydrophobic emulsion; the siloxane end in the perfluorosiloxane will hydrolyze to form silanol groups, which will then react and bond with the silanol groups on the surface of the silica sol to achieve fluorination modification of the silica sol nanoparticles. Tetraethyl orthosilicate, as a cross-linking agent, will cross-link with the fluorinated modified silica nanoparticles to form a three-dimensional network skeleton structure, which will not block the pores of the activated carbon and can improve the stability of the coating structure;
[0008] (4) Concentrating the super-hydrophobic emulsion by rotary evaporation at high temperature by 10 times, and then diluting it by 10 times with anhydrous ethanol, and repeating this process 1 to 3 times to obtain a moisture-proof modified emulsion; this method can remove volatile free perfluorosiloxane to prevent it from directly reacting with activated carbon and blocking the pores of the activated carbon;
[0009] (5) The activated carbon of step (2) is added to the moisture-proof modified emulsion for soaking, taken out after soaking, dried, and then soaked in a hydrochloric acid solution (the hydrochloric acid solution is used to remove the unreacted inorganic silica attached to the surface of the activated carbon, and to expand the pores of the activated carbon to avoid the reduction of the specific surface area of the activated carbon). After soaking, it is taken out and dried to obtain a hydrophobic modified activated carbon.
[0010] Among them, in step (1), the surface activation treatment of the activated carbon using an oxidant is specifically as follows: at room temperature, the activated carbon is added to hydrogen peroxide with a mass concentration of 10% and immersed for 60 minutes, and the mass ratio of the activated carbon to the hydrogen peroxide is 1:10.
[0011] Wherein, in step (2), the aqueous solution of hexadecyltrimethylammonium bromide is obtained by adding 0.1 parts by mass of hexadecyltrimethylammonium bromide to 100 parts by mass of water and stirring at 50°C.
[0012] Among them, 1 part by mass of the activated carbon after surface activation treatment is immersed in a hexadecyltrimethylammonium bromide aqueous solution, taken out after immersion, rinsed with clean water, and dried.
[0013] Wherein, in step (3), the added mass ratio of the silica sol to tetraethyl orthosilicate is 1:0.1-1. Tetraethyl orthosilicate will hydrolyze to form nanoparticles in an acidic system, and if the amount is too much, the coating strength will be reduced.
[0014] Wherein, in step (3), the added mass ratio of the silica sol to the perfluorosiloxane is 1:0.1. Adding too much perfluorosiloxane will also modify the activated carbon, thereby blocking its pores.
[0015] Wherein, in step (3), the temperature of the water bath heating is 50°C.
[0016] Wherein, in step (4), the temperature of the rotary evaporation concentration is 50°C.
[0017] Wherein, in step (5), the mass volume ratio of the activated carbon to the moisture-proof modified emulsion is 1:10.
[0018] Wherein, in step (5), the mass concentration of the hydrochloric acid solution is 10%; the drying temperature is 50° C., and the drying time is 6 hours.
[0019] The method of the present invention firstly activates the surface of activated carbon with a cationic surfactant to increase the adsorption sites on the surface and make the surface positively charged, and then coats the surface with negatively charged silicon dioxide nanoparticles to make the surface super-hydrophobic while avoiding clogging of internal pores.
[0020] Beneficial effects: Compared with the prior art, the present invention has the following significant effects: (1) The weight gain of the modified activated carbon of the present invention after being placed in a closed space with a relative humidity of 100% for 24 hours is less than 5%, and the weight gain of the modified activated carbon after being placed in a closed space with a relative humidity of 100% for 48 hours is less than 10%; (2) In a high humidity environment, the adsorption amount of the modified activated carbon of the present invention when adsorbing organic waste gas is increased by 3 to 5 times compared with the unmodified activated carbon; (3) When the modified activated carbon is used for sound absorption treatment of acoustic devices, the minimum resonance frequency F0 value is greater than 80 Hz. Compared with the existing modification method, which greatly reduces the acoustic performance of the activated carbon, the acoustic performance of the activated carbon obtained by the modification method of the present invention is almost equivalent to that before modification; (4) After the modified activated carbon of the present invention is saturated with adsorption, it is placed under vacuum or hot nitrogen conditions at 200 to 300°C for 1 hour, and the specific surface area of the regenerated activated carbon obtained can reach more than 90% of the specific surface area of the original activated carbon. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 SEM images of activated carbon at different magnifications before modification;
[0022] Figure 2 The results of the moisture absorption test of the activated carbon before and after modification in Example 1 are shown;
[0023] Figure 3 The photos of activated carbon before and after water adsorption in Example 1 are shown;
[0024] Figure 4These are the oil mist adsorption test results in a humid environment before and after the modified activated carbon in Example 1. DETAILED DESCRIPTION
[0025] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0026] Example 1
[0027] The method for preparing modified activated carbon with high regeneration rate and high specific surface area of the present invention comprises the following steps:
[0028] (1) At room temperature, add activated carbon to 10% hydrogen peroxide and soak for 60 minutes, with the mass ratio of activated carbon to hydrogen peroxide being 1:10. After soaking, take out and dry for later use;
[0029] (2) adding 0.1 parts of hexadecyltrimethylammonium bromide to 100 parts of deionized water and stirring at 50° C. for 30 min; placing 1 part of the activated carbon treated in step (1) in the hexadecyltrimethylammonium bromide aqueous solution and soaking it for 3 h, taking it out after soaking, rinsing it with clean water twice, and drying it for later use;
[0030] (3) 1 part of silica sol with a pH value of 4, a particle size of 4 nm, and a solid content of 15% was added to deionized water, and after ultrasonic mixing in an ultrasonic cleaning machine for 10 minutes, 80 mL of anhydrous ethanol was added thereto, and magnetic stirring was performed for 20 minutes to mix them evenly, and then 0.1 part of tetraethyl orthosilicate was added and stirred continuously, and finally 0.1 part of perfluorosiloxane was added dropwise using a pipette, and magnetic stirring was performed for 24 hours under heating in a water bath at 50° C. to obtain a super hydrophobic emulsion;
[0031] (4) concentrating the super hydrophobic emulsion by rotary evaporation at 50° C. by 10 times, and then diluting it by 10 times with anhydrous ethanol, and repeating the process twice to obtain a moisture-proof modified emulsion, wherein the solute content in the moisture-proof modified emulsion is 10 times the solute content in the super hydrophobic emulsion;
[0032] (5) Add 1 part of the activated carbon treated in step (2) to 10 parts of moisture-proof modified emulsion and soak for 12 hours. Take it out after soaking, dry it, and then put it into a hydrochloric acid solution with a mass concentration of 10% and soak it for 2 hours. Take it out after soaking and dry it at 50°C for 6 hours to obtain hydrophobic modified activated carbon.
[0033] After testing, the hydrophobic modified activated carbon obtained in Example 1 has a moisture absorption rate of 4.17% after being placed under 100% humidity for 24 hours. The specific surface area of the activated carbon before modification is 1360m 2 / g, the specific surface area of the hydrophobically modified activated carbon obtained in Example 1 is 1320m 2 / g.
[0034] Comparative Example 1
[0035] The preparation method of Comparative Example 1 is exactly the same as that of Example 1, except that the super-hydrophobic emulsion is concentrated 4 times by rotary evaporation at 50°C, and then diluted 4 times with anhydrous ethanol, and the process is repeated 2 times to obtain a moisture-proof modified emulsion, wherein the content of perfluorosilicone in the moisture-proof modified emulsion is 4 times lower than that in the super-hydrophobic emulsion; after testing, the hydrophobic modified activated carbon obtained in Comparative Example 1 has a moisture absorption rate of 9.18% under 100% humidity conditions for 24 hours, and a specific surface area of 1220 m 2 / g; the lowest resonance frequency F0 value after acoustic testing is 30Hz.
[0036] Comparative Example 2
[0037] The preparation method of Comparative Example 2 is exactly the same as that of Example 1, except that the super-hydrophobic emulsion is concentrated by rotary evaporation at 50°C by 6 times, and then diluted by 6 times with anhydrous ethanol, and the process is repeated twice to obtain a moisture-proof modified emulsion, wherein the content of perfluorosilicone in the moisture-proof modified emulsion is 6 times lower than that of the solute perfluorosilicone in the super-hydrophobic emulsion; after testing, the hydrophobic modified activated carbon obtained in Comparative Example 2 has a moisture absorption rate of 7.56% when placed under 100% humidity conditions for 24 hours, and a specific surface area of 1230 m 2 / g.
[0038] Comparative Example 3
[0039] The preparation method of Comparative Example 3 is exactly the same as that of Example 1, except that the super-hydrophobic emulsion is concentrated 8 times by rotary evaporation at 50°C, and then diluted 8 times with anhydrous ethanol, and the process is repeated twice to obtain a moisture-proof modified emulsion, and the content of perfluorosilicone in the moisture-proof modified emulsion is 8 times lower than that in the super-hydrophobic emulsion; after testing, the hydrophobic modified activated carbon obtained in Comparative Example 3 has a moisture absorption rate of 5.97% under 100% humidity conditions for 24 hours, and a specific surface area of 1260 m 2 / g.
[0040] It can be seen from Example 1 and Comparative Examples 1 to 3 that the more concentrated the carbon is, the less free fluorinated silicone is, the less activated carbon is blocked, and the less the specific surface area of the activated carbon is reduced; at the same time, the increase in concentration can increase the amount of hydrophobic nanoparticles loaded on the surface of the activated carbon, thereby increasing the moisture-proof performance of the activated carbon.
[0041] Test Example 1 Adsorption effect of activated carbon before and after modification in water bubbles and high humidity environment:
[0042] The unmodified activated carbon and the modified activated carbon of Example 1 were placed in water for 2 hours, and then placed in soybean oil, sunflower oil, sesame oil, n-hexane, n-decane and hexadecane respectively to compare the adsorption effects:
[0043] The unmodified activated carbon and the modified activated carbon of Example 1 were placed in a high humidity environment of RH = 99% for 2 hours and then taken out. Then, they were placed in soybean oil, sunflower seed oil, sesame oil, n-hexane, n-decane and hexadecane to compare the adsorption effects:
[0044] The test found that after water blistering, the unmodified activated carbon adsorbed 50.32 mg / g soybean oil, 112.07 mg / g sunflower oil, 82.47 mg / g sesame oil, 27.62 mg / g n-hexane, 48.78 mg / g n-decane, and 12.05 mg / g hexadecane. The modified activated carbon adsorbed 401.29 mg / g soybean oil, 1027.96 mg / g sunflower oil, 1175.88 mg / g sesame oil, 437.27 mg / g n-hexane, 632.84 mg / g n-decane, and 561.77 mg / g hexadecane.
[0045] During the water soaking process, the original activated carbon will quickly absorb a large amount of water molecules in the internal pore structure, and the surface will also be submerged in water, so it almost loses the adsorption effect on other organic substances. The modified activated carbon can float on the water surface, and the part in contact with the water surface will also form a layer of air film to prevent the entry of water, thus retaining good adsorption performance.
[0046] After being placed in a high humidity environment of RH = 99% for 2h, it was found that the adsorption capacity of unmodified activated carbon for soybean oil was 173.91mg / g, the adsorption capacity for sunflower oil was 141.84mg / g, the adsorption capacity for sesame oil was 194.24mg / g, the adsorption capacity for n-hexane was 202.38mg / g, the adsorption capacity for n-decane was 127.45mg / g, and the adsorption capacity for hexadecane was 229.17mg / g. The adsorption capacity of modified activated carbon for soybean oil was 415.63mg / g, the adsorption capacity for sunflower oil was 942.86mg / g, the adsorption capacity for sesame oil was 986.68mg / g, the adsorption capacity for n-hexane was 444.44mg / g, the adsorption capacity for n-decane was 532.84mg / g, and the adsorption capacity for hexadecane was 568.18mg / g.
[0047] This shows that after being placed in a high humidity environment for 2 hours, the unmodified activated carbon still adsorbed a large amount of water vapor during the process, so the adsorption performance was seriously lost. The modified activated carbon has good moisture resistance, adsorbs less water vapor, and the loss of adsorption capacity is much lower than that of the original activated carbon.
[0048] Verify whether the hydrophobic surface of the modified activated carbon in Example 1 blocks the internal pore structure of the activated carbon by measuring the adsorption capacity of the activated carbon before and after modification.
[0049] Specifically, the adsorption capacity of unmodified activated carbon on soybean oil is 523.81 mg / g, the adsorption capacity on sunflower oil is 1072.58 mg / g, the adsorption capacity on sesame oil is 1422.22 mg / g, the adsorption capacity on n-hexane is 400.09 mg / g, the adsorption capacity on n-decane is 584.27 mg / g, and the adsorption capacity on hexadecane is 517.55 mg / g. The adsorption capacity of modified activated carbon on soybean oil is 458.33 mg / g, the adsorption capacity on sunflower oil is 1153.85 mg / g, the adsorption capacity on sesame oil is 1225.64 mg / g, the adsorption capacity on n-hexane is 480.59 mg / g, the adsorption capacity on n-decane is 704.23 mg / g, and the adsorption capacity on hexadecane is 581.39 mg / g.
[0050] The experimental results show that the adsorption capacity of modified activated carbon for sunflower oil, n-hexane, n-decane and hexadecane increased, while the adsorption capacity for soybean oil and sesame oil decreased slightly, but the decrease was very small. The reason may be that the lipophilic hydrophobic functional groups exposed on the surface after modification have different affinities for different oil substances. Overall, the adsorption capacity of activated carbon does not change much after modification, indicating that the modified hydrophobic nanoparticle layer has little effect on the internal pores of the activated carbon and does not cause blockage problems in the internal pore structure of the activated carbon.
[0051] Verify the selective adsorption of edible oil mist by modified activated carbon in high humidity environment. Figure 4 It can be seen that under ambient humidity conditions, both the activated carbon before and after modification have a good adsorption effect on oil mist, and the weight gain of oil absorption is obvious. In a high humidity environment (relative humidity is 90%), the unmodified activated carbon will preferentially adsorb a large amount of water vapor, preventing the activated carbon from adsorbing oil mist; while the modified activated carbon has excellent moisture resistance, so it still maintains a high adsorption performance for edible oil mist in a high humidity environment, reflecting good selective adsorption.
[0052] Take the modified activated carbon of Example 1, soak it in hexadecane for 2 hours, and measure its adsorption capacity to be 583.45 mg / g. Then put it in an oven and bake it at 200°C for 2 hours, and measure its weight reduction to 579.78 mg / g, and calculate the hexadecane desorption rate to be 99.37%; soak it in hexadecane for 2 hours, and measure its adsorption capacity to be 577.93 mg / g, and calculate the hexadecane adsorption regeneration rate to be 99.05%. After 100 times of this reciprocation, the hexadecane desorption rate is 96.28%, and the hexadecane adsorption regeneration rate is 95.16%. Compared with the unmodified activated carbon, after the first adsorption, the hexadecane desorption rate is 53.56%, and the hexadecane adsorption regeneration rate is 55.29%.
Claims
1. A method for preparing modified activated carbon with high regeneration rate and high specific surface area, characterized in that: The steps include: (1) Activating the surface of activated carbon using an oxidant; (2) Soaking the activated carbon in an aqueous solution of hexadecyltrimethylammonium bromide, so that the surface of the activated carbon is charged with cations; (3) Acidic silica sol with a particle size of 4-10 nm and a solid content of 15-20% is added to water, and after ultrasonication, anhydrous ethanol is added, and after mixing, tetraethyl orthosilicate is added thereto, and stirring is continued. Finally, perfluorosiloxane is dropped into the solution, and stirring is performed under heating in a water bath to obtain a super hydrophobic emulsion; (4) Concentrating the super hydrophobic emulsion by 9 to 10 times by rotary evaporation at high temperature, and then diluting it by 9 to 10 times with anhydrous ethanol, and repeating this process 1 to 3 times to obtain a moisture-proof modified emulsion; (5) adding the activated carbon of step (2) into the moisture-proof modified emulsion for soaking, taking out and drying after soaking, and then soaking in the hydrochloric acid solution, taking out and drying after soaking to obtain the hydrophobic modified activated carbon; The moisture absorption weight gain of the modified activated carbon after being placed in a closed space with a relative humidity of 100% for 24 hours is less than 5%, and the moisture absorption weight gain after being placed in a closed space with a relative humidity of 100% for 48 hours is less than 10%; in a high humidity environment, when the modified activated carbon of the present invention adsorbs organic waste gas, the adsorption amount is increased by 3 to 5 times compared with the unmodified activated carbon; after adsorption saturation, the specific surface area of the regenerated activated carbon obtained by placing it under vacuum or hot nitrogen conditions at 200 to 300° C. for 1 hour can reach more than 90% of the specific surface area of the original activated carbon.
2. The method for preparing modified activated carbon with high regeneration rate and high specific surface area according to claim 1, characterized in that: In step (1), the surface activation treatment of the activated carbon using an oxidant is specifically as follows: at room temperature, the activated carbon is immersed in hydrogen peroxide having a mass concentration of 10-12%, and the mass ratio of the activated carbon to the hydrogen peroxide is 1-1.5:
10.
3. The method for preparing modified activated carbon with high regeneration rate and high specific surface area according to claim 1, characterized in that: In step (2), the hexadecyltrimethylammonium bromide aqueous solution is obtained by adding 0.1-0.2 parts by mass of hexadecyltrimethylammonium bromide to 100 parts by mass of water and stirring at 50-55°C.
4. The method for preparing modified activated carbon with high regeneration rate and high specific surface area according to claim 3, characterized in that: 1 part by mass of the activated carbon after the surface activation treatment was immersed in the aqueous solution of hexadecyltrimethylammonium bromide, taken out after immersion, rinsed with clean water, and dried.
5. The method for preparing modified activated carbon with high regeneration rate and high specific surface area according to claim 1, characterized in that: In step (3), the added mass ratio of the silica sol to tetraethyl orthosilicate is 1:0.1~1.
6. The method for preparing modified activated carbon with high regeneration rate and high specific surface area according to claim 1, characterized in that: In step (3), the added mass ratio of the silica sol to the perfluorosiloxane is 1:0.08-0.
1.
7. The method for preparing modified activated carbon with high regeneration rate and high specific surface area according to claim 1, characterized in that: In step (3), the temperature of the water bath heating is not less than 50°C.
8. The method for preparing modified activated carbon with high regeneration rate and high specific surface area according to claim 1, characterized in that: In step (4), the temperature of the rotary evaporation concentration is not higher than 50°C.
9. The method for preparing modified activated carbon with high regeneration rate and high specific surface area according to claim 1, characterized in that: In step (5), the mass volume ratio of the activated carbon to the moisture-proof modified emulsion is 1-1.5:
10.
10. The method for preparing modified activated carbon with high regeneration rate and high specific surface area according to claim 1, characterized in that: In step (5), the mass concentration of the hydrochloric acid solution is 10-15%; the drying temperature is not less than 50° C., and the drying time is 5-6 hours.
Citation Information
Patent Citations
Method for preparing silicon dioxide colloidal crystal film through gas-liquid interface method
CN106830700A
Damp-proof reproducible activated carbon and preparing method thereof
CN109647342A
Ecological treatment device for sewage treatment
CN111410315A
Hydrophobic metal oxide particle
JP2013103856A
Preparing method of enzyme immobilized silica
KR1020070118805A
